Incouple numbers and dedómetros: listening for meaning in bilingual children’s mathematical lexical inventions - Martínez Hinestroza, José; Peña-Pincheira, Romina S.; Adams Corral, Melissa (ZDM, 2023)
Previous research on bilingual mathematics education has proposed that as children “language mathematics” they use multiple sources of meaning. In this paper, we focus on lexical inventions—bilingual children’s made up words that are not formally defined or used but follow the phonology and morphology of a language—as a source of meaning. Consistent with tenets from translanguaging, we recognize lexical inventions as a creative language practice defying idealized language norms. A raciolinguistic theoretical perspective informs our interpretation of children, teachers, and researchers as listening subjects. The purpose of this paper is to explore how mathematical lexical inventions can prompt a translanguaging space where children, teachers, and researchers resist listening subject positions that predispose them to listen for predetermined language practices. Drawing on two lesson transcripts, one from a fourth-grade English-immersion classroom in Colombia and one from a third-grade Spanish-immersion classroom in the United States, we used moment analysis in translanguaging spaces to identify spontaneous and critical moments where lexical inventions prompted mathematical explorations. We argue for adopting listening subject positions as learners of transgressive language practices that are part of interactions between children and mathematics.